Enhancing Performance and Commitment Through Justice - Ade Irma Anggraeni (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
Employee commitment is one of the determining factors for the excellence of Government institutions in optimizing public services. This study aims to examine and analyze organizational commitment, namely affective commitment, continuing commitment, normative commitment in the relationship between organizational dimensions of justice, namely distributive justice, procedural justice, interactional justice on employee performance. There were 175 employees as respondents of the research of the Agricultural Human Resources Extension Development Agency of the Ministry of Agriculture in East Java. The sampling technique in the study used a probability sampling technique where the respondents had the same opportunity to be selected. The data collection method used a questionnaire. data analysis using the Partial Least Square (PLS).